Design and Development of the Sidajaya Tourism Village Information and Promotion Media - Rahayu, Slamet; Tri Herdiawan Apandi; Taufan Abdurrachman; Nurfitria Khoirunisa; Adi Firmansyah; Asep Saepuloh (Yayasan Kita Menulis, 2025)
The potential of Sidajaya Tourism Village, which is not yet known to many people, has hampered the development of this tourist village. Information about the Sidajaya tourist village is still difficult to access, making people reluctant to look for the information they need, so knowledge about it is limited. Therefore, a system is needed to help the public access information about the Sidajaya tourist village. This research aims to build a website-based Sidajaya Tourism Village Information System as a medium for information and promotion. This system was built using the PHP programming language and MySQL database, with data collection methods through observation and interviews. The system development stage includes analysis, design, implementation, and testing. The result of developing this system is a website that allows the public to search for information about the Sidajaya tourist village easily and supports more efficient promotion and management to increase tourist visits.